A Synthetic Analog of the Mineral Ivanyukite: Sorption Behavior to Lead Cations - Gleb O. Samburov; Galina O. Kalashnikova; Taras L. Panikorovskii; Vladimir N. Bocharov; Aleksandr Kasikov; Ekaterina Selivanova; Ayya V. Bazai; Daria Bernadskaya; Viktor N. Yakovenchuk; Sergey V. Krivovichev (Crystals, 2022)
The production of electrolytic nickel includes the stage of leaching of captured firing nickel matte dust. The solutions formed during this process contain considerable amounts of Pb, which is difficult to extraction due to its low concentration upon the high-salt background. The sorption of lead from model solutions with various compositions by synthetic and natural titanosilicate sorbents (synthetic ivanyukite-Na-T (SIV), ivanyukite-Na-T, and AM-4) have been investigated. The maximal sorption capacity of Pb is up to 400 mg/g and was demonstrated by synthetic ivanyukite In solutions with the high content of Cl− (20 g/L), extraction was observed only with a high amount of Na (150 g/L). Molecular mechanisms and kinetics of lead incorporation into ivanyukite were studied by the combination of single-crystal and powder X-ray diffraction, microprobe analysis, and Raman spectroscopy. Incorporation of lead into natural ivanyukite-Na-T with the R3m symmetry by the substitution 2Na+ + 2O2− ↔ Pb2+ + □ + 2OH− leds to its transformation into the cubic P−43m Pb-exchanged form with the empirical formulae Pb1.26[Ti4O2.52(OH)1.48(SiO4)3]·3.32(H2O).